P229 Clinician and community collaboration on PrEP in the UK – a narrative. (30th June 2016) - Portman, Mags; Owen, GrEG; Quinn, Killian; Craddock, Alex; Thompson, Marc; Nwokolo, Nneka; Reeves, Iain; Bayley, Jake; Brady, Michael; Nutland, Will; McCormack, Sheena
Abstract : Background: The PROUD study showed that PrEP can be successfully provided via sexual health clinics in the UK. The delay in widespread availability of PrEP has seen renewed grassroots activism from the community sector. Methods: We document the timeline and benefits of a close relationship between community activists and clinicians in advancing the PrEP agenda. Results: Community engagement during the PROUD trial led on to increased advocacy and activism from October 2014 when interim results were published. Launch of the websites IWantPrEPNow.co.uk (with a click to buy generic PrEP) and PrEPster.info in October 2015 further galvanised clinicians and community advocates into greater joined up action. The benefits of this included: 1) Mutual social media support; advancing the PrEP agenda amongst potential PrEP users and clinicians, 2) Obtaining GMC input on providing clinical advice regarding generics, 3) Pushing for free monitoring for current generic PrEP users, 4) Sharing of therapeutic drug monitoring data, 5) Community input into staff training and service development such as production and review of patient information, and 6) Two way learning; sharing PrEP users perspective and evidence based research. Discussion/conclusion: The lack of availability of PrEP in the UK is proving a challenge to both community advocates and clinicians. We wish to celebrate the achievements made within the confines of the current political climate, in particular working to ensure patient safety. There is a history of successful clinician/community collaboration in GUM/HIV medicine; with an NHS England PrEP roll out we need to reflect this to drive uptake. If NHS England decides against PrEP funding, we suggest that continued collaboration, support and innovation will be paramount.